2007
DOI: 10.1590/s0100-879x2007000100010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral ingestion of an extract of the herb Uncaria tomentosa on the biodistribution of sodium pertechnetate in rats

Abstract: The aim of the present study was to determine the effect of the oral ingestion of an extract of the herb Uncaria tomentosa (cat's claw) on the biodistribution of the radiobiocomplex sodium pertechnetate (Na 99m TcO 4 ) in rats. The animals (male Wistar rats, 2 months old, 180-220 g), were treated (1 mL) with an U. tomentosa extract (32 mg/mL, N = 5) or 0.9% NaCl solution (control, N = 5) for 7 days. After this period, Na 99m TcO 4 (3.7 MBq, 0.3 mL) was injected through the ocular plexus and after 10 min the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
0
14
0
1
Order By: Relevance
“…It can reduce the uptake of radiobiocomplex sodium pertechnetate in heart (Moreno et al 2007a). Again, this may decrease the visualization of the organ, requiring a repeat procedure.…”
Section: Heartmentioning
confidence: 99%
“…It can reduce the uptake of radiobiocomplex sodium pertechnetate in heart (Moreno et al 2007a). Again, this may decrease the visualization of the organ, requiring a repeat procedure.…”
Section: Heartmentioning
confidence: 99%
“…It has already reported that the biodistribution of radiopharmaceuticals used in diagnostic imaging in nuclear medicine is also altered by including plant origin drugs (Hesslewood & Leung, 1994;Britto et al, 1998;Gomes et al, 2001;Mattos et al, 1999). It has been described that extracts of medicinal plants could interfere with the biodistribution of 99m Tc sodium pertechnetate particularly (Rebello et al, 2007;Rebello et al, 2008;Bernardo-Filho et al, 2005;Moreno et al, 2007;Jankovic & Djokic, 2005;Valenca et al, 2005). In these studies, alterations on the uptake of radiopharmaceutical were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Radiobiocomplexes may be prepared with technetium-99m (Tc-99m), as sodium pertechenetate ( 99m TcO 4 Na), and used as imaging agents (Hladik III et al, 1987;Saha, 2004). The bioavailability of radiobiocomplexes can be recognizably altered by a wide variety of conditions, such as, drug therapy, radiation therapy, diseases and medicinal plant therapy Oliveira et al, 2003;Bernardo-Filho et al, 2005;Moreno et al, 2007a;Moreno et al, 2007b). As the investigation of herbs interaction with cells is highly relevant and necessary, and also there are studies suggesting the association of some constituents of Ginkgo biloba (EGb) with possible toxic effects, the purpose of this work was: (i) to evaluate the influence of a Ginkgo biloba extract (EGb 761) on the ultrastructure (electronic microscopy) of some organs isolated from Wistar rats treated with this extract and (ii) to assess the effect of this extract on the biodistribution of the sodium pertechnetate.…”
Section: Introductionmentioning
confidence: 99%